Comunicação e mobilização social no processo de regularização fundiária: um caminho para a habitação saudável - CORRÊA, Débora Cristina Salomão (2022)
The present work starts from the premise that communication in the construction of social mobilization must be one of the first steps in the process of land regularization, aiming at improving the housing of residents of informal urban centers. There are many failures in the mobilization of social actors which, consequently, are reflected in the later stages of regularization. Thus, we seek to outline a methodological proposal in order to implement communicative strategies in land regularization projects involving mobilizing agents, social actors and institutional managers, in order to guarantee the establishment of co-responsibility of the process in REURB-S projects, developed by the REDE AMAZÔNIA program. . The objective of the research is to subsidize support material and support for the preparation of a communication and social mobilization plan in the next municipalities where the Amazon Network Program operates, articulating, from an interdisciplinary perspective, concepts of communication, social mobilization and healthy housing, in the search for social inclusion of informal urban centers. The analysis of the results shows that most residents would like to receive better direct instructions from the regularization teams to understand the entire process. Among the alternatives, we sought to include digital media, podcasts, lives, among others, as viable tools for training, information, and mobilization. It is proposed, as a communicative strategy for future mobilizations in the partner municipalities of the Amazon Network Program, the use of usual means of interaction between people, such as social networks and digital media.